Poor Places, Thriving People : How the Middle East and North Africa Can Rise Above Spatial Disparities - World Bank (World Bank, 2012)
The main messages of poor places, thriving people: how the Middle East and North Africa can rise above spatial disparities can be summarized in four words: people, connections, clusters, and institutions. This report shows how smart investments and policies in transport can connect poor places to the dynamic economies of their rich neighbors. There is also a wide open field of opportunity for telecommunications to bring electronic proximity to lagging areas. Many countries have spent huge sums on subsidies to entice investors to lagging areas-usually without any sustainable impact. This report recommends that governments turn their efforts toward the new approach to local economic development, which is gaining ground around the world, and is based on economic clusters, local competitive advantage, private initiative, and public-private dialogue. The report describes the state-of-play in territorial planning, public financial management, targeted programs, deconcentration, and decentralization, and it sketches some emerging lessons. This report combines the insights of specialists in the majority of the World Bank's key sectors: agriculture, development economics, education, health, poverty analysis, social protection, and transport. It is the report's modest aim, if not to offer a single formula for reducing spatial disparities, at least to propose a range of policy options that the region's leaders can reflect on in the light of their national objectives.